Building inclusive early learning environments for children with a disability in low-resource settings: Insights into challenges and opportunities from rural Zimbabwe - Tafirenyika, Joice; Mhizha, Samson; Ejuu, Godfrey (Frontiers in Education, 2023)
The majority of young children with a disability live in low- and middle-income countries, where access to inclusive early learning programs supported by governments or non-government organizations is usually unavailable for the majority of the population, who live in rural areas. This study explored the feasibility of leveraging materials and personnel available within local communities to provide inclusive early learning programs in rural Zimbabwe. Caregivers of young children with some disability were given the opportunity to describe their experienced challenges; ways in which they informally support their children’s early learning; and the types of skills and resources they were able and willing to offer to support the establishment and operation of a more formal group-based inclusive early learning program. Qualitative data were generated from a purposive sample of caregivers of children with diverse impairments (n = 12) in two remote rural districts in Zimbabwe. Themes were identified in the rich qualitative data caregivers provided during individual interviews. The challenges caregivers experienced included the failure of interventions to improve their children’s level of functioning, the lack of access to assistive devices, the perception that the local school would be unable to accommodate their children, and worry about the future. Despite these stressors, caregivers actively supported their children’s self-care, social, moral and cognitive development and sought ways to save the funds that would be needed if their children could attend school. Caregivers were also willing and able to provide diverse forms of support for the establishment and operation of an inclusive early education program: food, funding, teaching and learning materials, and free labor. The insights obtained from these data informed the design of local community-controlled inclusive early education programs and the types of support caregivers and children may need to participate fully in these.